Comparison of Rehabilitation Outcomes Between Surgical and Conservative Treatments for Incomplete Intertrochanteric Proximal Femur Fractures—A Retrospective Cohort Study - Cheuk Kin Kwan; Yu Hei Choi; Rossetti Hiu Yin Lam; Richard Ku; Tsz Hang Ma; Wing Hong Liu; Wing Hoi Cheung; Chaoran Liu; Sheung Wai Law; Ronald Man Yeung Wong (Journal of Clinical Medicine, 2026)
Background/Objectives: Incomplete intertrochanteric proximal femur fractures pose a management dilemma regarding the choice between surgery and conservative care. This study compared radiographic and functional outcomes between surgical fixation and conservative treatment and evaluated whether immediate full weight-bearing (FWB) can be performed by conservatively managed patients. Methods: This is a retrospective cohort study of consecutive patients aged ≥ 60 who presented with MRI-confirmed incomplete intertrochanteric fractures at a tertiary trauma center and rehabilitation unit from 2010 to 2020. Clinical outcomes were compared between conservatively managed and surgically treated patients. The primary outcome was radiographic bone union at 3 months; the secondary outcomes included secondary displacement, mobility at discharge, hospital length of stay, and mortality at 3 months and 1 year. Results: Forty-two patients met the inclusion criteria: 10 were managed conservatively, and 32 were managed operatively. Baseline age and sex distributions were similar between groups. At 3 months post-injury, bone union rates were 100% in both groups, with no incidences of secondary displacement regardless of whether a course of protected weight-bearing was prescribed. Functional mobility at discharge and length of stay were comparable. Mortality at 3 months and 1 year did not differ significantly between groups. Conclusions: The preliminary findings of this retrospective cohort study demonstrated managing MRI-diagnosed incomplete intertrochanteric proximal femur fractures conservatively to be feasible. Despite the limited sample size, all included patients who were treated conservatively achieved bone union by 3 months without secondary displacement. Their clinical outcomes were also comparable to the outcomes of those who were treated with surgical fixation. However, given the small sample size and lack of randomization, further investigation is warranted before clinical application.